Micronesia & Pacific Islands [videorecording (DVD)] - McCormick, Megan. (Megan Leah); Wright, Ian, 1965- (Pilot Film & Television, 2009)
"Micronesia: Globe Trekker Megan McCormick begins her journey on modern westernized Guam and then flies to Pohnpei, the capital of Micronesia. After a stop in the state of Chuuk, she goes kayaking through the magnificent rock islands of the Republic of Palau. Megan ends her trip cycling the ancient land of Yap and attends the island's annual celebration ; Pacific Islands: Globe Trekker Ian Wright begins his Pacific adventure diving in Fiji. He flies to Vanuatu to meet a tribal chief and climb the world's most accessible active volcano. He ends his journey wreck diving and discovers the bloody World War II history of the Solomon Islands"--Container.